O INOVADOR NÃO ESTÁ ONDE SE PENSA: PERFIS INOVADORES NAS REDES SOCIAIS ORGANIZACIONAIS - Assis, Walber Santos de (2013)
This research paper aims to contribute towards a more in depth understanding of the management and the innovation of the formation of more sustainable organizations, focusing on the use of more creative and innovative people on the social network sectors with the objective of better structured networks as well as with a better performance from their collaborators and talents. Therefore, a variable study confronts the results obtained from the Social Network Analysis with the ones from MBTI Inspiira version, the first one observed what the network understands about people and the second observed what people's preferences were, highlighting the most important characteristics for the development of an innovative network. Moreover it can be said that there are many actors with innovative profiles who are close to these networks, in other words, they are open to helping this process of change, innovation and its way of management . Unfortunately due to various factors not taken into account in this study, they are not being used to their full potential which could lead to the innovative management of this network and therefore lead to a better sustainability of these organizations.